Sexual Dimorphism in Histological Structure of Normal Rat Stomach - Zhu,Lei (Sociedad Chilena de Anatomía, 2016)
Fifty male and fifty female Spargue-Dawley rats were randomly chosen and used to study the sexual dimorphisms of stomachic histological structures. The rat stomach consisted of the nonglandular part and the glandular part. The gender differences of the nonglandular part existed in the thicknesses of the stratified squamous epithelium and the longitudinal muscle. These findings revealed that the male rat stomach may storage more foods than the female. The gastric glands occupied all the lamina propria in the glandular part. The thicknesses of the gastric glands of the female and male rat were 525.0 ± 95.9 µm and 472.0 ± 158.7 µm respectively, and the difference was very significant (p<0.01). The gastric glands could be divided to two layers in the HE stain, i.e. the luminal and the basal layers. The thicknesses of the luminal layer of the female and male rat were 289.7 ± 95.9 µm and 300.0 ± 120.7 µm respectively, and the difference was insignificant (p>0.05). On the contrary, the thicknesses of the basal layer and the three muscle layers in the female glandular part were all thicker than those in male, and the differences were very significant (P<0.01). These findings indicated that the female rat stomachs may have a more powerful digestive ability than the male ones. The nucleus-glandular index of the gastric gland of the normal female and male rat were 0.19 ± 0.05 and 0.18 ± 0.04 respectively, and the difference was insignificant (p>0.05).